Help Rendered by Thozhi for Love Marriage - R, Elavarasu (International Research Journal of Tamil, 2020)
We know that In Sangam Literature Thozhi (A Close Friend of Heroine) played a vital roll in hero and heroine’s life before and after their marriage. The parents have all rights to make arrangement of marriage for their daughter for their own wish. But, once a woman fall in love with a man and she would like to marry that man, in this situation the help rendered by Thozhi is inevitable. This article focuses to research the roll of Thozhi in hero and heroine’s love marriage which have been recorded in Sangam literature. The above said performance of Thozhi reflected her minute knowledge about human life, her fond of love on the heroine and smart action etc., Sangam literature recorded many knowledgeable and important activities of Thozhi. This article is like to reveal the various performances of Thozhi in the love marriage proposal of hero and heroine.